ANALISIS SEKTOR UNGGULAN DAN PENGARUHNYA TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN MIMIKA - Ida Adriyani (JURNAL KRITIS (Kebijakan, Riset, dan Inovasi), 2018)
Ida Adriyani. 2018. Leading Sector Analysis and Its Effect on the Original Income of Mimika Regency (Supervised by Ida Ayu Purba Riani and Transna Putra Urip). The aims of this research are: (a) know and analyze the economic sectors that have the potential to be developed as leading sectors in Mimika Regency in 2010 - 2017; (b) knowing and analyzing the influence of the leading sectors on Regional Original Revenue in Mimika Regency 2010 - 2017. The data used in this research are secondary data sourced from BPS Mimika Regency, Papua Province BPS and Mimika Regency Regional Revenue Agency. Data is collected using the documentation method. To answer the formulation of this problem of research, the analytical tool used is Location Quotient (LQ) analysis and multiple linear regression analysis. Based on the results of the analysis, it is known that: (a) The leading sectors in Mimika Regency are the Agriculture, Forestry and Fisheries sectors, as well as the Mandatory Administration, Defense and Social Security sectors, where both sectors have LQ values ​​of more than 1 and are classified in sectors advanced and growing rapidly; (b) The superior sector of the Mimika Regency consisting of the Agriculture, Forestry and Fisheries sectors, as well as the Government Administration, Defense and Social Security sectors must have a significant effect on the Mimika Regency PAD as indicated by the acquisition of F count of 11,352 which is greater than the Ftable value of 5 , 79 at a 90% confidence level.